2018
DOI: 10.1007/s10461-018-2237-8
|View full text |Cite
|
Sign up to set email alerts
|

Does Quality of Life and Sexual Quality of Life in HIV Patients Differ Between Non-treated HIV Controllers and Treated Patients in the French ANRS VESPA 2 National Survey?

Abstract: People living with HIV who spontaneously control the virus without antiretroviral treatment are called HIV Controllers and their status places them at the limits of bio-clinical normality. The objective of this study was to investigate an unexplored field: HIV Controllers' quality of life (QOL). Using quantitative methods, we compared the QOL of untreated (by definition) HIV Controllers in the ANRS CO18 HIV Controller cohort study, with the QOL of treated patients in the French national survey ANRS VESPA 2. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Being born in metropolitan France was associated with better scores in the MC and TI dimensions. Even if in the general population, individuals from sub-Saharan Africa reported better mental HRQL (27), in many other context as COVID-19 pandemic, ethnic minorities are recognized as vulnerable to COVID-19 (41) (42), mostly because of their low health literacy and their precarious life conditions (42) (43), including high prevalence of comorbidities (44). Consistent to our study, Drewes and a. underlined that infection, social circumstances, relationships problems, comorbidities (including hypertension), and stigma could have negatively impact the HRQL of PLWHA (45).…”
Section: Discussionmentioning
confidence: 86%
“…Being born in metropolitan France was associated with better scores in the MC and TI dimensions. Even if in the general population, individuals from sub-Saharan Africa reported better mental HRQL (27), in many other context as COVID-19 pandemic, ethnic minorities are recognized as vulnerable to COVID-19 (41) (42), mostly because of their low health literacy and their precarious life conditions (42) (43), including high prevalence of comorbidities (44). Consistent to our study, Drewes and a. underlined that infection, social circumstances, relationships problems, comorbidities (including hypertension), and stigma could have negatively impact the HRQL of PLWHA (45).…”
Section: Discussionmentioning
confidence: 86%
“…In a recent prospective study, HIC reported a slight but significant increase in their quality of life after 24–48 weeks of ART [23] . However, another study reported higher scores in physical and social quality of life for HIC than non-controller treated participants, but lower scores in mental quality of life, interpretated as being associated with the uncertainty of the disease evolution [40] . Further studies are required to investigate the effect of ART on HIC quality of life.…”
Section: Discussionmentioning
confidence: 95%
“…Measuring QOL, and its associated factors, is important as it helps understanding the impact of health status on the different aspects of a patient’s daily life. QOL is a complex concept, that not only refers to health but also refers to interactions people have with their living environment [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The World Health Organization (WHO) defines quality of life (QOL) as "an individual's perception, of his/her place in the existence, in the context of the culture and value system in which she/he lives, in relation to his/her objectives, expectations, standards and concerns" [9]. Measuring QOL, and its associated factors, is important as it helps understanding the impact of health status on the different aspects of a patient's daily life.…”
Section: Introductionmentioning
confidence: 99%